Ionic micro-structure and transport properties of low-temperature aluminium electrolytes containing potassium cryolite and sodium cryolite. Issue 30 (17th July 2019) - Lv, Xiaojun; Han, Zexun; Guan, Chaohong; Jiang, Liangxing; Wu, Shangyuan
Abstract : Insight into the ionic micro-structure and transport properties of low-temperature aluminium electrolytes containing potassium cryolite and sodium cryolite at an atomic level. Abstract : Nowadays, low-temperature aluminium electrolytes are reported to have good prospects for application in the industrial process of aluminium production. In this paper, low-temperature electrolytes containing potassium cryolite and sodium cryolite with a cryolite ratio of 1.3 were investigated by using first-principles molecular dynamics simulation. This calculation reproduces the ionic structure of low-temperature 1.3(KF + NaF)–AlF3 electrolytes, indicating that [AlF4 ] −, [AlF5 ] 2− and [AlF6 ] 3− are the fundamental aluminum–fluoro clusters and [AlF5 ] 2− is the predominant species. The calculated results for the ionic structure indicate that molten 1.3(KF + NaF)–AlF3 electrolytes have a high ionic polymerization degree, which is unfavorable for the transport properties of low-temperature 1.3(KF + NaF)–AlF3 electrolytes. Fortunately, increasing the mass fraction of NaF can effectively reduce the polymerization degree of ionic structure and thus improve the ionic conductivity of low-temperature 1.3(KF + NaF)–AlF3 electrolytes, which is an important guiding factor for the component selection of low-temperature electrolytes in future. Also, DFT calculations were adopted to further analyse the small aluminum–fluoro complexes. The calculated Raman spectrum of the aluminum–fluoro complexes is excellently consistent with literature results. Our calculated ionic conductivity falls in between the estimated value of the empirical equation of different literature studies, demonstrating that our results may be more precise than the literature results. This further proves the practicability of our modified N–E equation.